2020
DOI: 10.3390/ma13081834
|View full text |Cite
|
Sign up to set email alerts
|

Formula-Driven, Size-Tunable Synthesis of PMMA Nanoparticles by Varying Surfactant Concentration

Abstract: In this communication, we present a streamlined, reproducible synthetic method for the production of size-tunable poly(methyl methacrylate) (PMMA) nanoparticles (PMMANPs) and amine-functionalized block-copolymer PMMANPs (H2N-PMMANPs) by varying subcritical concentrations (i.e., below the concentration required to form micelles at 1 atm and 20 °C) of sodium dodecyl sulfate (SDS). We plotted the Z-average size data against SDS concentration, which revealed a second-order exponential decay function, expressed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
(31 reference statements)
1
5
0
Order By: Relevance
“…Table 2 shows the parameters of the fitted function to relate the change in PMMA sphere diameter as a function of SDS surfactant concentration. The results of this investigation are similar to those found by other authors on the change of PMMA sphere size as a function of SDS surfactant concentration, in which they report a nonlinear behavior, although with a second-order exponential decay function [28]. Although surfactant concentration was similar, the particle size intervals show considerable differences in nanoparticle sizes (20-97 nm) relative to this work.…”
Section: Fit a Functionsupporting
confidence: 90%
See 3 more Smart Citations
“…Table 2 shows the parameters of the fitted function to relate the change in PMMA sphere diameter as a function of SDS surfactant concentration. The results of this investigation are similar to those found by other authors on the change of PMMA sphere size as a function of SDS surfactant concentration, in which they report a nonlinear behavior, although with a second-order exponential decay function [28]. Although surfactant concentration was similar, the particle size intervals show considerable differences in nanoparticle sizes (20-97 nm) relative to this work.…”
Section: Fit a Functionsupporting
confidence: 90%
“…The equation modeling the diameter size of PMMA spheres as a function of % SDS is valid between 120 to 360 nm. Kamras et al reported the validity of a second-order exponential decay equation between 20 and 97 nm [28]. Other works reported a relationship with particle size between 300 and 1000 [28,44].…”
Section: Fit a Functionmentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, the inherent agent re-design possibilities for He-Ne laser and AgPP NP can influence improved treatment outcomes. In this regard, we have expertise in metallic polymeric NP size tunability [32], Ag-PMMA cargo delivery with PAA synthesis stability for longer circulating times [29], and the use of light to treat central nervous system heterogeneic brain disorders [33].…”
Section: Inherent Challenges To Expected Outcomesmentioning
confidence: 99%